Feedback Control of p53 Translation by REDD1 and mTORC1 Limits the p53-Dependent DNA Damage Response - Vadysirisack, Douangsone D. (American Society for Microbiology, 2011)

(untitled)
Exquisite control of the level and activity of p53 are required in order to preserve cellular homeostasis following DNA damage. How this regulation is integrated with other key metabolic pathways in vivo is poorly understood. Here, we describe an endogenous feedback circuit for regulation of p53 through its transcriptional target gene, Redd1, a stress-induced inhibitor of TOR complex 1 (TORC1) activity. Cells and tissues of Redd1(−/−) mice exhibit enhanced sensitivity to ionizing radiation and chemotherapy treatment, which we demonstrate is attributable to abnormally increased p53 protein level and activity in the absence of Redd1. We find that deregulation of p53 in this setting is not due to failed DNA repair or to increased p53 stabilization but, instead, to increased p53 translation. We show that Redd1 loss leads to elevated mammalian TORC1 (mTORC1) activity, which explains the increased p53 translation and protein levels. Together, these findings suggest that REDD1-mediated suppression of mTORC1 activity exerts feedback control on p53, thereby limiting the apoptotic response and contributing to cellular survival following DNA damage. This work therefore defines a role for REDD1 in the control of p53 in vivo, with potential therapeutic implications for cancer and for the variety of genetic diseases involving TOR pathway signaling components.